Effects of mild psychological stress on facial impressions - Koizumi, Koyo; Hirao, Naoyasu; Yamanami, Haruna; Ohira, Hideki (Frontiers in Psychology, 2023)
Introduction Appearance plays an important role in maintaining a positive impression in social interactions. Psychological stress is known to have an adverse effect on facial skin, as indicated in previous studies. However, no study has investigated the negative effect of stress on facial impressions. Therefore, we aimed to investigate changes in impressions from facial images before and after mental stress tasks using an online survey. Method Thirteen Japanese men were recruited to have their facial photographs taken before and after undergoing a psychological stress task. We observed the physiological effects of an increased heart rate and decreased blood flow on the cheek skin. Four average facial images were created for each time point (control: “baseline;” stress: “0H,” “1H,” and “3H”) from their facial photographs. An online survey was conducted with 700 Japanese participants, who compared the “baseline” to other images and selected one of two options in each of the six questionnaire items of impressions. Results The results showed that the rate of participants who chose “baseline” was significantly lower in the items “looks tired,” “looks old,” and “looks irritated” and higher in “looks clean-cut” and “looks healthy” compared to other images created from photographs after the stress task (“0H,” “1H,” and “3H”). Conclusion These results suggest that psychological stress loading not only causes physiological changes in autonomic nervous activity and skin blood flow but also negatively impacts facial impressions for a few hours following a mild stress load.